Coal Plant Repurposing for Ageing Coal Fleets in Developing Countries - Energy Sector Management Assistance Program (World Bank, Washington, DC, 2021)
Coal plants worldwide are grappling with low-capacity utilization levels and environmental issues; and have not only become unprofitable to utilities, but also uneconomical to customers. Developed countries with significant coal capacities such as Australia, Canada, Germany, the United Kingdom (UK), and the United States (US), are taking different approaches to wean away from coal. One such approach includes retiring and repurposing coal plants for various productive end uses, including solar plants, wind plants, data centers, and energy storage. Developing countries may gain much from the experience of their developed counterparts. Against this backdrop, the authors briefly examine the power situation in three developing countries, namely, South Africa, Chile, and India, based on their economic prowess within respective regions, predominance of coal in economic activities, and vulnerability to climate change, which make an interesting case for an analysis of repurposing coal plants in developing countries. This study presents the concepts and components of a cost-benefit analysis needed for a coal plant repurposing project.